2023
DOI: 10.31234/osf.io/t9r43
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to Higher Rates of False News Erodes Media Trust and Fuels Overconfidence

Abstract: What are the effects of false news exposure on downstream trust and belief? In two online experiments (N participants = 2,735, N observations = 49,158) we investigated whether exposure to high proportions of false news could have deleterious effects by sowing confusion and fueling distrust in both true and false news. In a between-subjects design where U.S. participants rated the accuracy of true and false news, we manipulated the proportions of false news participants were exposed to (17%, 33%, 50%, 66% 83%).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is also important to keep in mind that the contrast effect we demonstrate here is not incompatible with a simultaneous assimilation effect (wherein exposure to a high prevalence of implausible claims shifts people's sense of veracity base rates and increases overall belief) (12,13). The combination of a more liberal plausibility threshold for classifying news as true (contrast effect) and an increased bias towards judging headlines as false (assimilation effect) can lead to net increased belief in ambiguous news.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is also important to keep in mind that the contrast effect we demonstrate here is not incompatible with a simultaneous assimilation effect (wherein exposure to a high prevalence of implausible claims shifts people's sense of veracity base rates and increases overall belief) (12,13). The combination of a more liberal plausibility threshold for classifying news as true (contrast effect) and an increased bias towards judging headlines as false (assimilation effect) can lead to net increased belief in ambiguous news.…”
Section: Discussionmentioning
confidence: 56%
“…While recent work has shown that prior exposure to the same false story can make that story more believable (9)(10)(11), it is not clear whether exposure to one set of implausible claims in news could make other, unrelated stories seem more or less plausible by contrast. On the one hand, a high prevalence of implausible news stories could make consumers more generally skeptical, falling for fewer inaccurate headlines while also disbelieving accurate ones (12,13). Such an assimilation effect would converge with similar work on the role of prevalence in perceptual signal detection (14), in which a high prevalence of signals (in this case, implausible news stories) can make them easier to accurately recognize.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, there can be substantial heterogeneity in exposure to informational quality at the individual level by source (Lin et al, 2023b), within platforms (Guess et al, 2020;González-Bail ón et al, 2023), when there are algorithmic changes (Guess et al, 2023), across platform (Allcott et al, 2019), or between topics (Praet et al, 2022). Our results suggest that different intuitions can develop, including feelings of skepticism in low quality environments (Altay et al, 2023), under this heterogeneity and that overly wide priors can be misapplied when shifts in the environment are not salient. Of additional concern is the possibility that misinformation purveyors can hijack or create high-quality environments to push specific misinformation more effectively (Stewart et al, 2022).…”
Section: Introductionmentioning
confidence: 82%
“…Recent studies have shown that the information composition of the information environment, specifically the relative proportion of true to false information, can significantly influence participants' susceptibility to misinformation 27,28 . Notably, Orchinik et al 27 found that participants were more likely to erroneously classify false (true) information as true (false) when exposed to predominantly true (false) information in the experimental information environment, suggesting that participants responses were biased in the direction of the "veracity base rate" (see also 28 ).…”
Section: Nudge-based Misinformation Interventions Are Effective In In...mentioning
confidence: 99%